2014
DOI: 10.1039/c4cc00473f
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric fluorescence assay for γ-glutamyltranspeptidase detection based on a single fluorophore via analyte-induced variation of substitution

Abstract: The first ratiometric fluorescent probe for γ-glutamyltranspeptidase (GGT) was developed, which functions through GGT-induced variation of substitution and subsequent changes in photophysical properties. It can detect GGT in human serum, and be used to visualize the endogenous GGT in ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…Here we have performed such an assay by using a mixed serum sample from healthy people and three individual serum samples from liver cancer patients. As shown in Table 1, the GGT level in the mixed healthy human serum is 66.50 U/L, which is in coincidence with the normal serum GGT level (5 -85 U/L), 15 whereas those in two serum samples from liver cancer patients are over 100 U/L, which exceeds the normal range. However, one of the serum samples from the liver cancer patients shows unexpectedly the same GGT level as that from the healthy people, namely obviously a false-negative result.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Here we have performed such an assay by using a mixed serum sample from healthy people and three individual serum samples from liver cancer patients. As shown in Table 1, the GGT level in the mixed healthy human serum is 66.50 U/L, which is in coincidence with the normal serum GGT level (5 -85 U/L), 15 whereas those in two serum samples from liver cancer patients are over 100 U/L, which exceeds the normal range. However, one of the serum samples from the liver cancer patients shows unexpectedly the same GGT level as that from the healthy people, namely obviously a false-negative result.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…It was found that the fluorescence enhancement was directly proportional to the GGT concentration in the range of 1 -50 U/L, with a linear equation of ΔF = 16.1  C (U/L) + 7.8 (R = 0.996), where ΔF is the increase of fluorescence intensity with and without GGT (Figure 2). Moreover, a good linear fluorescence response of CV-Glu still holds even at lower concentrations (0 -100 mU/L) of GGT (Figure S11); in this case, the detection limit (3S/m, where S is the standard deviation of blank measurements, n = 11, and m is the slope of the linear equation) was determined to be 5.6 mU/L GGT, which is one of the most sensitive fluorescent probes 15. Then the Michaelis constant (K m ) of CV-Glu reacting with GGT was calculated by using Lineweaver-Burk plot (Figure S12in the Supporting Information).…”
mentioning
confidence: 99%
“…And this technique has been extensively applied in the research of various enzyme-catalyzed processes [51][52][53][54][55]. [56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…no. 23266; Thermo Fisher Scientific, Inc.) was used to detect caspase-3 and caspase-9 activity according to the manufacturer's protocol (19). In brief, vaginal epithelial cells were lysed in lysis buffer (Beyotime Biotechnology, Nantong, Jiangsu, China) and centrifuged at 18,000 x g for 10 min at 4˚C and supernatants were collected.…”
Section: Cell Viability Assaymentioning
confidence: 99%